Determinants of Global Value Chain Participation : Cross-Country Evidence - Fernandes, Ana; Kee, Hiau Looi; Winkler, Deborah (World Bank, Washington, DC, 2020)
The past decades witnessed big changes in international trade with the rise of global value chains. Some countries, such as China, Poland, and Vietnam, rode the tide, while other countries, many in the Africa region, faltered. This paper studies the determinants of participation in global value chains, based on empirical evidence from a panel data set covering more than 100 countries over the past three decades. The evidence shows that factor endowments, geography, political stability, liberal trade policies, foreign direct investment inflows, and domestic industrial capacity are very important in determining participation in global value chains. These factors affect participation in global value chains more than traditional exports.